Berat Beban yang Dijunjung Mengakibatkan Perbedaan Keluhan Muskuloskeletal dan Kelelahan serta Kontribusinya Terhadap Produktivitas Kerja Buruh Angkut di Pasar Badung - Ni Putu Apriantini; I Made Sutajaya; Ni Putu Sri Ratna Dewi; Nyoman Wijana; Desak Made Citrawathi (Undiksha, 2022)
This study aims to determine the weight of the load upheld resulting in differences in musculoskeletal complaints and fatigue and its contribution to the productivity of transport workers. The location of this research is Badung Market, Denpasar. Analysis of the data used in this study is the Independent Sample t-test and regression test at a significance level of 5%. The results of the data analysis used were data on the difference between musculoskeletal complaints and fatigue, because the pre-test data between group I (carrying weight ≤ 25 kg) and group II (carrying weight > 25 kg) were not compatible. The results of the analysis showed that there was a significant difference in musculoskeletal complaints of 22.28% with a p value of 0.0001 (p <0.05) and 15.16% of fatigue with a p value of 0.0001 (p <0.05). ) between group I and group II. The results of the Regression test to determine the contribution of musculoskeletal complaints and fatigue to work productivity, showed that musculoskeletal complaints did not contribute to the work productivity of transport workers, because the obtained p value = 0.907 in group I and p = 0.927 in group II (p> 0.05) . Fatigue also did not contribute to the work productivity of transport workers, because the obtained p value = 0.498 in group I and p value = 0.583 in group II (p> 0.05). Based on this analysis, it can be concluded that the weight of the load being upheld results in differences in musculoskeletal complaints and fatigue in the transport workers, but does not contribute to the work productivity of the transport workers.